Hepatitis B, Hepatitis C and HIV seroprevalence among Syrian refugees: A cross-sectional study from a tertiary referral center in Turkey - Bayram Yeşil (Journal of Surgery and Medicine, 2019)
Aim: Hepatitis B (HBV), Hepatitis C (HCV) and Human Immunodeficiency Virus (HIV) cause serious health problems all over the world. Due to the recent conflicts and war in Syria, many immigrants have entered Turkey in a controlled and / or uncontrolled manner. In this study, we aimed to determine HBV, HCV, and HIV seroprevalence among Syrian migrants who were referred to our hospital.Methods: This cross-sectional study was performed between 01/01/2015 - 14/05/2018 in Ankara Yuksek Ihtisas Training and Research Hospital. Serum samples from patients were evaluated for positivity of HBV surface antigen (HBsAg), antibodies against HBV surface antigen (anti-HBs), HCV antibody (anti-HCV) and anti-HIV with the Enzyme-Linked Immunosorbent Assay (ELISA) method.Results: Among 244 patients included in the study, 154 were male (63.11%) and 90 were female (36.89%). Seroprevalences of HBV were 5.84% and 5.55%, respectively, the difference between which was statistically insignificant (P>0.05). Anti-HCV was positive in 6 (2.46%) patients. HCV seroprevalence rates were 1.29% in men, and 4.44% in women. None of these 244 patients had anti-HIV positivity.Conclusion: In our study, we found that the seroprevalences of HBV and Anti-HIV in Syrian migrants were similar to domestic values, but that of anti-HCV was higher. Age-related incidence rates also differed. We believe that the knowledge of these data is important in terms of planning preventive and therapeutic measures for migrants.